Targeting mitochondria: restoring the antitumor efficacy of exhausted T cells - Mei-Qi Yang; Shu-Ling Zhang; Li Sun; Le-Tian Huang; Jing Yu; Jie-Hui Zhang; Yuan Tian; Cheng-Bo Han; Jie-Tao Ma (Molecular Cancer)
Abstract Immune checkpoint blockade therapy has revolutionized cancer treatment, but resistance remains prevalent, often due to dysfunctional tumor-infiltrating lymphocytes. A key contributor to this dysfunction is mitochondrial dysfunction, characterized by defective oxidative phosphorylation, impaired adaptation, and depolarization, which promotes T cell exhaustion and severely compromises antitumor efficacy. This review summarizes recent advances in restoring the function of exhausted T cells through mitochondria-targeted strategies, such as metabolic remodeling, enhanced biogenesis, and regulation of antioxidant and reactive oxygen species, with the aim of reversing the state of T cell exhaustion and improving the response to immunotherapy. A deeper understanding of the role of mitochondria in T cell exhaustion lays the foundation for the development of novel mitochondria-targeted therapies and opens a new chapter in cancer immunotherapy.